2022
DOI: 10.1038/s41598-022-12496-8
|View full text |Cite
|
Sign up to set email alerts
|

Endosymbiotic Chlorella variabilis reduces mitochondrial number in the ciliate Paramecium bursaria

Yuuki Kodama,
Masahiro Fujishima

Abstract: Extant symbioses illustrate endosymbiosis is a driving force for evolution and diversification. In the ciliate Paramecium bursaria, the endosymbiotic alga Chlorella variabilis in perialgal vacuole localizes beneath the host cell cortex by adhesion between the perialgal vacuole membrane and host mitochondria. We investigated whether host mitochondria are also affected by algal endosymbiosis. Transmission electron microscopy of host cells showed fewer mitochondria beneath the algae-bearing host cell cortex than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…(Kitatani and Kodama, unpublished data). A previous study demonstrated that the number of host mitochondria and trichocysts was significantly reduced with increasing numbers of endosymbiotic algae [ 24 , 25 , 34 ]. Similarly, algal reinfection may decrease the number of host crystals.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…(Kitatani and Kodama, unpublished data). A previous study demonstrated that the number of host mitochondria and trichocysts was significantly reduced with increasing numbers of endosymbiotic algae [ 24 , 25 , 34 ]. Similarly, algal reinfection may decrease the number of host crystals.…”
Section: Discussionmentioning
confidence: 99%
“…1 N cells [ 24 ]. Strain 1N was identified as C. variabilis by rbcL gene analysis [ 25 ]. Moreover, P. multimicronucleatum strain YM-25 (syngen 2, mating type III or IV [cycler]) was used.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Algae-free P. bursaria cells are smaller in size compared to algae-bearing cells, and their proliferation rate significantly weakens [ 67 , 69 , 71 ]. The presence of endosymbiotic Chlorella also significantly reduces the number of host mitochondria, accompanied by a lower content of mitochondrial proteins compared to algae-free host cells [ 72 ]. Notably, separated P. bursaria and Chlorella can readily form new symbiotic combinations by mixed together.…”
Section: Ciliates and Intact Algal Symbiontsmentioning
confidence: 99%